Burden of puerperal sepsis and its relation with maternal mortality - Kaur, Harpreet; Kaur, Sarvjeet; Mattu, Sheena; Nandrajog, Anchal (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Puerperal sepsis, an infection of the genital tract, can appear at any time between the time of membrane rupture or labour to 42nd day after delivery. It accounts for 15% of maternal mortality. Aims of this study are to determine the incidence of puerperal sepsis and the associated mortality rate and explore socioeconomic risk factors of puerperal sepsis. Methods: This prospective longitudinal study was conducted in Obstetrics and Gynecology department at the GGSMC and H, Faridkot, from November 2021 to October 2022. Inclusion criteria were: any patient presenting either immediately after delivery/abortion or within 42 days of these events with fever and any of the following: abdominal pain, malodorous lochia, abdominal distention, uterine tenderness, pelvic abscess, peritonitis, mechanical or foreign body injury, organ failure, or shock. Results: The incidence of puerperal sepsis among the women was 6.37 per 100 population at-risk in our study sample. Laparotomies were performed on 17 patients, primarily because to abdominal collection. Four patients experienced uterine perforation, and one of them also had gastrointestinal injury. The maternal deaths attributed to puerperal sepsis were 19.2%. Conclusions: The morbidity and mortality of women from puerperal sepsis are indicators of the quality of obstetric care in the area. The incidence of maternal sepsis may be reduced with the support of initiatives to encourage early recognition and effective therapy. Future study must focus on exploring the causes of anaemia and the factors that influence women going to unsafe delivery and abortions, so that evidence-based policies at the community level.